THE INFLUENCE OF CUSTOMER INVOLVEMENT IN MEMORABLE CUSTOMER EXPERIENCE (MCE) IN MEDIATING THE EFFECT OF EXPERIENTIAL MARKETING ON REVISIT INTENTION AT BEACHWALK BALI - I Dewa Bagus Mahesa Gangga (Review of International Economy and Finance, 2026)
This study aims to analyze the effect of experiential marketing on revisit intention through the mediating role of memorable customer experience among visitors of Beachwalk Bali. The study employed a quantitative approach with an associative research design grounded in the Stimulus–Organism–Response (SOR) theory. A total of 160 respondents were selected using purposive sampling techniques. Data were collected through Likert-scale questionnaires and analyzed using Hayes PROCESS Macro Model 4 with a bootstrapping approach. The findings reveal that experiential marketing has a positive and significant effect on both memorable customer experience and revisit intention. Memorable customer experience also exerts a positive and significant influence on revisit intention and is proven to partially mediate the relationship between experiential marketing and revisit intention. These findings indicate that a memorable shopping experience can enhance visitors’ intentions to revisit Beachwalk Bali.